Optimization of Hole Cleaning and Cuttings Removal in High Inclined Till Horizontal Well - Mohammed, Karrar Ahmed; A. Al-Haleem, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The goal of this experimental study is to determine the effects of different parameters (Flow rate, cuttings density, cuttings size, and hole inclination degree) on hole cleaning efficiency. Freshwater was used as a drilling fluid in this experiment. The experiments were conducted by using flow loop consist of approximately 14 m (46 ft) long with transparent glass test section of 3m (9.84 ft.) long with 4 inches (101.6 mm) ID, the inner metal drill pipe with 2 inches (50.8 mm) OD settled with eccentric position positive 0.5. The results obtained from this study show that the hole cleanings efficiency become better with high flow rate (21 m3/hr) and it increase as the hole inclination angles increased from 60 to 90 degree due to dominated of the rolling force. The cuttings size has negative influence on cuttings recovered as size increased and that is true for all cuttings specific gravity due to direct effect of the cuttings size and density on the gravity force which work against lifting force. The increasing of hole inclination angle above 60 degree will affect positively on cuttings removal efficiency.